Degree of angle closure and extent of peripheral anterior synechiae: an anterior segment OCT study. Issue 1 (21st June 2007) - Su, D H W; Friedman, D S; See, J L S; Chew, P T K; Chan, Y-H; Nolan, W P; Smith, S D; Huang, D; Zheng, C; Li, Y; Foster, P J; Aung, T
Abstract : Aims: To evaluate the relationship between angle width as determined by anterior segment optical coherence tomography (AS-OCT) and the presence of peripheral anterior synechiae (PAS). Methods: This was a prospective observational case series in which 203 subjects with primary angle closure or open angles were recruited. Images of the nasal, temporal and inferior angles were obtained with AS-OCT in dark conditions. Subjects then underwent gonioscopy by an independent examiner who was masked to the AS-OCT findings. PAS were identified by gonioscopy and defined as abnormal adhesions of the iris to the angle that were at least half a clock hour in width and present to the level of the anterior trabecular meshwork or higher. The total clock hours of PAS were recorded. Results: Sixty-eight subjects (33.5%) were PACS, 76 subjects (37.4%) had PAC/PACG, 14 (6.9%) had primary open angle glaucoma, and 45 (22.2%) subjects were normal with open angles. There was a weak but significant correlation between the angle opening distance (AOD), trabecular iris space area (TISA) and angle recess area (ARA) with clock hours of PAS (Spearman's correlation coefficients = −0.30, −0.32 and −0.32, respectively, p<0.001). The mean values of the AOD, TISA and ARA in the nasal, temporal and inferior quadrants were significantly less in eyes with PAS compared with those without (p<0.001, Mann–Whitney U test). Analysis by quadrant showed that these parameters were smaller in the nasal and temporal quadrants in eyes with PAS (p<0.01). Conclusions: Angle width determined by AS-OCT and the extent of PAS were weakly correlated, and angle width was significantly smaller in eyes with PAS.